ANALISIS KEBUTUHAN MATERI PEMBELAJARAN KARYA ILMIAH BERBAHASA PRANCIS - Herman, Herman (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2019)
(Title: Needs Analysis of Learning Materials For French Academic Writing). This study aims to describe the needs of material for French academic writing courses. it shows 66.70% of respondents need to learn specific grammar to increase its effectiveness; 54.20% of respondents need special learning about essential terms for linguistic, literary or language teaching; 79.20% think that specialised terminology is needed to write research background. 54.20% thought that writing practice was very necessary, while 70.80% hoped there would be reading cativity for some scientific articles. 53.40% of respondents consider it necessary to master the logical connector of French. In addition, 50% of respondents think that a French scientific writing course is required and 25% want this to be mandatory. 62.50% expect this course to have at least 3 credits: 1 credit for writing theory and 2 credits for writing practice. Keywords: need Assessment, Frenchacademic writing